Solubilization of n-hexadecane by micellar solutions of trehalolipid - surfactants of biological origin - I. A. Nechaeva; A. S. Parfenova; A. S. Filippova; A. E. Filonov (Тонкие химические технологии)
Objectives. To isolate biosurfactants of glycolipid nature produced by oil hydrocarbon degrading bacteria and to establish their ability to solubilize hydrophobic compounds in the case of n-hexadecane.Methods. Trehalolipids were isolated from bacteria Rhodococcus erythropolis X5 (VKM Ac-2532 D) and Rhodococcus erythropolis S67 (VKM Ac-2533 D) included in the MikroBak biopreparation for the bioremediation of oil-contaminated territories. The genome of R. erythropolis X5 is deposited in the National Center for Biotechnology Information database under GenBank accession numbers CP044283 and CP044284, BioSample – SAMN12818508, BioProject – PRJNA573614, and SRA – PRJNA573614. The content of trehalolipid biosurfactants was estimated by the amount of trehalose in aqueous solutions of biosurfactants using the phenolsulfur method. The surface tension of the obtained aqueous solutions of biosurfactants was determined by the du Noüy ring method using a Kruss K6 tensiometer (Kruss, Germany). The critical concentration of micelle formation was determined by the inflection point on the curves of surface tension dependence on the concentration of the biosurfactant solution. In order to establish the solubilizing ability of biosurfactants, the residual concentration of n-hexadecane in an aqueous sample of different concentrations was determined using a gas chromatographic method of analysis.Results. At a constant surface tension of 24.2 mN/m and 25.0 mN/m for R. erythropolis X5 and R. erythropolis S67, respectively, the critical micelle concentration for both strains was 33 mg/L (3.8 ∙ 10−5 mol/L). The solubilizing effect of Rhodococcus trehalolipid micellar solutions against hydrophobic n-hexadecane was demonstrated by gas chromatographic analysis. The solubilization process was characterized using molar solubilization capacity (Sm), molar solubilization ratio (MSR), micelle–water partition coefficient (Km), and solubilization energy 0 (ΔGS ). It was shown that the solubilization process of n-hexadecane proceeds spontaneously 0 (ΔGS = −35.5 kJ/mol) and more efficiently (Sm = 4.3 mol/mol, MSR = 4.7 mol/mol) than in comparison with other biosurfactants of glycolipid nature.Conclusions. Based on the value of the molar solubilization coefficient, it can be concluded that trehalolipids of the R. erythropolis X5 strain solubilize n-hexadecane in aqueous solutions to a greater extent than compared to other biosurfactants of a glycolipid nature, but are inferior to synthetic surfactants.